Percutaneous screw fixation for trapezium fracture - Nallathambi, Vetri R.; V., Raviraman (International Journal of Research in Orthopaedics, 2022)
Isolated trapezial fracture is a rare diagnosis which can lead to long term symptoms if missed. We report a case of vertical intra-articular displaced trapezial fracture treated with percutaneous cancellous screw fixation with good functional outcome.